Strategi Pengembangan Mitra dan Implementasi Warkop Digital Oleh PT. Cybers Global Indonesia Dalam Mendukung Revolusi Industri 5.0 di Indonesia - Asri Nalistia; Nani Septiana; Febriyanto (Jurnal Manajemen DIVERSIFIKASI, 2026)
Technological development has become a major driver in social, economic, and cultural transformation around the world. In Indonesia, the entry of the industrial revolution 4.0 era has changed the paradigm of human activities from manual to digital. PT Cybers Global Indonesia, a company committed to advancing Indonesia towards the era of industrial revolution 5.0, is one of the pioneers in supporting the digital transformation. One of its business units, Warkop Digital, is a coffee shop concept that integrates digital services with internet technology, providing access to information and opportunities to develop village potential. This research explored the partner development strategy and implementation of Warkop Digital by PT Cybers Global Indonesia in supporting the industrial revolution 5.0 in Indonesia. Although still in its early developmental stages, Warkop Digital had successfully reached 26 partnerships from 14 Provinces in Indonesia. However, the biggest challenge faced was how to expand this concept widely throughout Indonesia with a limited number of partners. Thus, this study aimed to investigate effective strategies to expand the reach of Warkop Digital so that it can have a broader impact on economic and social development in Indonesia.